2016
DOI: 10.1073/pnas.1600558113
|View full text |Cite
|
Sign up to set email alerts
|

DELAY OF GERMINATION1 ( DOG1 ) regulates both seed dormancy and flowering time through microRNA pathways

Abstract: Seed germination and flowering, two critical developmental transitions in plant life cycles, are coordinately regulated by genetic and environmental factors to match plant establishment and reproduction to seasonal cues. The DELAY OF GERMINATION1 (DOG1) gene is involved in regulating seed dormancy in response to temperature and has also been associated genetically with pleiotropic flowering phenotypes across diverse Arabidopsis thaliana accessions and locations. Here we show that DOG1 can regulate seed dormanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
149
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 162 publications
(168 citation statements)
references
References 70 publications
8
149
0
1
Order By: Relevance
“…miRNAs, and namely miR156, have been implicated in the regulation of the transition to germination (Huang et al 2013). Very recently, the DELAY OF GERMINATION1 (DOG1) gene has been shown to regulate seed dormancy, and flowering times, in response to temperature by affecting the levels of miR156 and miR172 (Huo et al 2016). In fact, the authors showed that miR156 and miR172 affect seed germination.…”
Section: Seed Dormancy and Transition To Germinationmentioning
confidence: 99%
See 2 more Smart Citations
“…miRNAs, and namely miR156, have been implicated in the regulation of the transition to germination (Huang et al 2013). Very recently, the DELAY OF GERMINATION1 (DOG1) gene has been shown to regulate seed dormancy, and flowering times, in response to temperature by affecting the levels of miR156 and miR172 (Huo et al 2016). In fact, the authors showed that miR156 and miR172 affect seed germination.…”
Section: Seed Dormancy and Transition To Germinationmentioning
confidence: 99%
“…As suggested by Luo et al (2006), the strong expression of miR397 in pro-embryogenic cells results in downregulation of laccase genes. These interactions may be fundamental for maintaining the characteristic thin walls of the embryonic cells and their meristematic Huo et al (2016) features. Inversely, decreasing the expression of miR397 allows laccases to accumulate, with a resulting lignification of cell walls during the transition from meristematic to a mature cell state (Luo et al 2006).…”
Section: Functional Characterization Of Srnas and Their Targets In Sementioning
confidence: 99%
See 1 more Smart Citation
“…Genetically, DOG1 has been shown to control a gibberellin-dependent endosperm-weakening mechanism in Arabidopsis and other Brassicaceae family members (12). DOG1 is also required for the miRNA156-mediated delay of flowering and germination (13).…”
mentioning
confidence: 99%
“…Significantly associated hits are distributed across 30 different genes on four different chromosomes (1, 2, 4, and 5), as shown in the Shared Genes view in easyGWAS and in Supplemental Data Set 1. The 87 shared peaks include the dormancy regulator DOG1 (At5g45830), which has recently been shown to affect flowering time (Huo et al, 2016); FLOWERING LOCUS C (FLC; At5G10140), and FRIGIDA (At4G00650), which are linked to flowering time variation Amasino, 1999, 2001;Méndez-Vigo et al, 2013, 2016Sanchez-Bermejo and Balasubramanian, 2016); and ANTHOCYANINLESS2 (ANL2; At4G00730), which is involved in root development (Kubo and Hayashi, 2011). Furthermore, easyGWAS makes it possible to investigate the LD and gene information in close proximity to a focal SNP.…”
Section: Case Study In Arabidopsismentioning
confidence: 99%